Simple Approach to Enhance Green Tea Epigallocatechin Gallate Stability in Aqueous Solutions and Bioavailability: Experimental and Theoretical Characterizations - Philippe-Henri Secretan; Olivier Thirion; Hassane Sadou Yayé; Thibaud Damy; Alain Astier; Muriel Paul; Bernard Do (MDPI AG, 2021)
Because of its antioxidant, antimutagenic, and anti-infectious properties, epigallocatechin gallate (EGCG) is the most interesting compound among the green tea catechins polyphenols. However, its health effects are inconclusive due to its very low bioavailability, largely due to a particular instability that does not allow EGCG to reach the potency required for clinical developments. Over the last decade, many efforts have been made to improve the stability and bioavailability of EGCG using complex delivery systems such as nanotechnology, but these efforts have not been successful and easy to translate to industrial use. To meet the needs of a large-scale clinical trial requiring EGCG in a concentrated solution to anticipate swallowing impairments, we developed an EGCG-based aqueous solution in the simplest way while trying to circumvent EGCG instability. The solution was thoroughly characterized to sort out the unexpected stability outcome by combining experimental (HPLC-UV-mass spectrometry and infrared spectroscopy) and computational (density functional theory) studies. Against all odds, the EGCG-sucrose complex under certain conditions may have prevented EGCG from degradation in aqueous media. Indeed, in agreement with the ICH guidelines, the formulated solution was shown to be stable up to at least 24 months under 2-8 °C and at ambient temperature. Furthermore, considerable improvement in bioavailability in rats, against EGCG powder formulated in hard-gel capsules, was shown after gavage. Thus, the proposed formulation may provide an easily implementable platform to administer EGCG in the context of clinical development.